Crop diversification for enhancing productivity, profitability and resource use efficiency of rice (Oryza sativa)-based systems in red and lateritic soils of eastern region - SAHA, BISWAJIT; BARIK, ARUN KUMAR; MANDAL, NAKUL (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at agricultural farm, Institute of Agriculture, Visva-Bharati, West Bengal to identify most productive, remunerative and resource use efficient rice (Oryza sativa L.)-based cropping systems in red and lateritic soil during 2014–15 and 2015–16. Pooled data of two years field experiments revealed that highest productivity of rice was achieved from legume involved system, viz. rice-potato-green gram (4.81 t/ha) followed by rice-yellow sarson-green gram (4.67 t/ha) and rice-lentil-okra (4.64 t/ha) which were at par with each other. Highest system rice equivalent yield (SREY) was found in rice-baby corn-elephant foot yam (31.89 t/ha/yr) which was at par with rice-french bean-baby corn (30.99 t/ha/yr). Rice-baby corn-elephant foot yam system achieved significantly higher system gross return (`4,22,467/ha) and net return (`2,69,557/ha) over other systems. However, significantly higher system return per rupee investment was obtained from rice-lentil-okra (`3.12). Significantly higher system production efficiency/SPE (129.14 kg/ha/day) and higher employment potential (345 man days/ha/yr) was found in rice-french bean-baby corn. Highest land use efficiency (LUE) was in rice-lentil-elephant foot yam system (94.5%) followed by rice-baby corn-elephant foot yam (86.3%) and rice-potato-sesame (73.9%). Rice-french bean-baby corn also showed highest system energy output (1344.14 GJ/ha), energy output:input ratio (43.47), energy output efficiency (4.99 GJ/ ha/day) and highest energy productivity (6448.35 kg REY/GJ). This was similar with rice-yellow sarson-baby corn sequence. Hence, inclusion of vegetables (french bean, baby corn, elephant foot yam) in rice-based cropping systems enhanced the productivity, profitability, energy use efficiency and employment potential over traditional cropping sequences like rice-potato-green gram and rice-potato-sesame in red and lateritic soil of eastern region.